Autophagy Induction Ameliorates Inflammatory Responses in Intestinal Ischemia–Reperfusion Through Inhibiting NLRP3 Inflammasome Activation. Issue 3 (September 2019) - Wang, Zishuo; Li, Zhenlu; Feng, Dongcheng; Zu, Guo; Li, Yang; Zhao, Yan; Wang, Guangzhi; Ning, Shili; Zhu, Jie; Zhang, Feng; Yao, Jihong; Tian, Xiaofeng
Abstract : ABSTRACT: Intestinal ischemia/reperfusion (I/R)-induced systemic inflammation leads to multiple organ dysfunction syndrome. Previous studies have indicated that the NOD-like receptor protein (NLRP)3 inflammasome modulates intestinal inflammation; however, the pathophysiological mechanisms remain unclear. Autophagy is a critical metabolic mechanism that promotes cellular survival following ischemic injury. Recently, basal autophagy has been implicated in the alleviation of extensive inflammation. However, the role of autophagy in NLRP3 inflammasome activation in intestinal I/R-induced inflammatory injury remains undefined. In the present study, we examined whether NLRP3 inflammasome activation is induced in mice subjected to intestinal I/R injury, which is measured as increased apoptosis-associated speck-like protein containing a CARD levels, caspase-1 activity, and interleukin-1β (IL-1β) secretion. Importantly, the in-vitro results showed that NLRP3 knockdown decreases proinflammatory cytokine production and increases resistance to hypoxia/reoxygenation (H/R)-triggered inflammation. Subsequently, we demonstrated a critical role for autophagy in suppressing intestinal I/R-induced NLRP3 inflammasome activation in vivo . Furthermore, we showed that the loss of autophagy activates inflammasome-mediated IL-1β secretion, which aggravates H/R injury, and NLRP3 knockdown reverses these effects. Collectively, these results directly implicated the homeostatic process of autophagy and NLRP3 inflammasome in ischemic bowel disease and identified a novel pathway for therapeutic intervention in intestinal I/R.